Exposure Route of TiO2 NPs from Industrial Applications to Wastewater Treatment and Their Impacts on the Agro-Environment - Zahra Zahra; Zunaira Habib; Sujin Chung; Mohsin Ali Badshah (Nanomaterials, 2020)
The tremendous increase in the production and consumption of titanium dioxide (TiO2) nanoparticles (NPs) in numerous industrial products and applications has augmented the need to understand their role in wastewater treatment technologies. Likewise, the deleterious effects of wastewater on the environment and natural resources have compelled researchers to find out most suitable, economical and environment friendly approaches for its treatment. In this context, the use of TiO2 NPs as the representative of photocatalytic technology for industrial wastewater treatment is coming to the horizon. For centuries, the use of industrial wastewater to feed agriculture land has been a common practice across the globe and the sewage sludge generated from wastewater treatment plants is also used as fertilizer in agricultural soils. Therefore, it is necessary to be aware of possible exposure pathways of these NPs, especially in the perspective of wastewater treatment and their impacts on the agro-environment. This review highlights the potential exposure route of TiO2 NPs from industrial applications to wastewater treatment and its impacts on the agro-environment. Key elements of the review present the recent developments of TiO2 NPs in two main sectors including wastewater treatment and the agro-environment along with their potential exposure pathways. Furthermore, the direct exposure routes of these NPs from production to end-user consumption until their end phase needs to be studied in detail and optimization of their suitable applications and controlled use to ensure environmental safety.